Solid-phase synthesis and cytotoxic evaluation of novel pyridinium bromides - Sadaiyan Govindaraj; Kilivelu Ganesan; Perumal Elumalai; Rajanathadurai Jeevitha; Jospin Sindya; Subramani Annadurai; Shiek S. S. J. Ahmed; Mudassar Shahid (Scientific Reports)
Abstract A series of amide-based mono and dimeric pyridinium bromides were synthesized using conventional and microwave-assisted solvent-free methods. The quaternization reactions of m-xylene dibromide and 4-nitrobenzylbromide with amide-based substituted pyridine proceeded efficiently, whereas 1,6-dibromohexane required reflux conditions. A comparative analysis of the solvent-free microwave-assisted reactions revealed a significant reduction in reaction time (up to 20-fold) and increased yields, accompanied by simplified work-up procedures. Notably, these reactions exhibited 100% atom economy and generated no environmental waste. The cytotoxic effects of the synthesized compounds were assessed using the MTT assay, nuclear staining, and Real Time-Polymerase Chain Reaction (PCR) on the lung cancer cell line (A-549).Molecular docking studies were performed to investigate the interaction and binding of B-Raf kinase inhibitors with the amide-based mono and dimeric pyridinium bromides. Furthermore, the toxicity of the drug molecules was assessed using the BOILED-Egg plot at the central nervous system.